Role of Stem Cells in Dentistry: A Review - Satabdi Pattanaik1 , Shashirekha Govind2 , Lora Mishra3 , Debkant Jena3 , Siba Prasad Jena1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current strategy of dental treatment is based on 3 elements- restore, retain and revitalize. Replacingthe lost or diseased tissue with the same natural tissue is a challenge in the field of dentistry. Keepingthis in mind, the use of stem cells has emerged as a potential way for its ideal replacement. Stem cells areundifferentiated cells, which can differentiate or multiply into particular types of cells and tissues. Besidesstem cells, scaffolds and growth factor abandoned their role in the field of regeneration. Stem cells can beeasily isolated from the orofacial region and have the property to differentiate into osteogenic, odontogenic,adipogenic, neurogenic components. This review article will discuss both embryonic and adult stem cells,sources, and their role in the process of regeneration along with tissue engineering strategy.